Organometallic Aspects of Fluoroalkylation Reactions with Copper and Nickel - Wang, Huan; Vicic, David A. (Synlett, 2013)
The development of perfluoroalkylation methods has become increasingly important in synthetic chemistry. However, many of the metal-mediated transformations that occur readily with alkyl substrates can proceed slowly, with limited scope, or not proceed at all with fluoroalkyl derivatives. To develop more sophisticated transformations with fluoroalkyl groups using base metals, a better understanding of their fundamental fluoro-organometallic chemistry is needed.This account describes our recent investigations into the organometallic chemistry of well-defined nickel– and copper–fluoroalkyl complexes, as well as our efforts towards trifluoromethoxylations and trifluoromethylthiolations using those metals. Synthetic routes to the new complexes are discussed, as are their structural and electrochemical properties and chemical reactivities.1 Introduction2 Bottling a Copper(I)–Trifluoromethyl Source3 The Redox Chemistry of Copper– and Nickel–Fluoroalkyl Complexes4 Nickel- and Copper-Mediated Trifluoromethylthiolations5 The Organometallic Chemistry of Nickel–Perfluoroalkyl Complexes6 Outlook
Keywords: trifluoromethylation; cross-coupling; nickel; copper; fluorine